Does cotinine act upon reactive oxygen species and peroxidases? - Vellosa, José Carlos Rebuglio; Maissar Khalil, Najeh; da Fonseca, Luiz Marcos; Brunetti, Iguatemy Lourenço; Oliveira, Olga Maria Mascarenhas de Faria (Eclética Química, 2007)
Nicotine, an oxidizing agent, is certainly one of the most widely used alkaloids in the world. It is, together with its main metabolite, cotinine, responsible for tobacco-dependence. The use of tobacco is closely associated with lung disease, morphological leukocyte modification and generation of oxidant species. The aim of this study was to look for a possible relationship between cotinine, oxidant species generation and oxidative processes. After studying the action of cotinine in some chemical oxidation models and on the enzymatic kinetics of peroxidases (myeloperoxidase and horseradish peroxidase), we concluded that cotinine does not act directly upon H2O2, HOCl, taurine chloramines, horseradish peroxidase or myeloperoxidase.